Mathematical Methods for Engineers and Scientists 1 Complex Analysis, Determinants and Matrices - Tang, Kwong-Tin.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2007)
Pedagogical insights gained through 30 years of teaching applied mathematics led the author to write this set of student oriented books. Topics such as complex analysis, matrix theory, vector and tensor analysis, Fourier analysis, integral transforms, ordinary and partial differential equations are presented in a discursive style that is readable and easy to follow. Numerous clearly stated, completely worked out examples together with carefully selected problem sets with answers are used to enhance students' understanding and manipulative skill. The goal is to make students comfortable and confident in using advanced mathematical tools in junior, senior, and beginning graduate courses.
Complex Analysis -- Complex Numbers -- Complex Functions -- Complex Series and Theory of Residues -- Determinants and Matrices -- Determinants -- Matrix Algebra -- Eigenvalue Problems of Matrices.
Keywords: Mathematical physics; Applied mathematics; Engineering mathematics; Theoretical, Mathematical and Computational Physics; Mathematical and Computational Engineering